A study on the timing of small-bowel capsule endoscopy and its impact on the detection rate of bleeding sources - Daisuke Kametaka; Masaya Iwamuro; Toshihiro Inokuchi; Seiji Kawano; Sakiko Hiraoka; Motoyuki Otsuka (BMC Gastroenterology)
Abstract Background Small-bowel capsule endoscopy (SBCE) is an essential diagnostic tool for obscure gastrointestinal bleeding, particularly for identifying bleeding sources in the small intestine. The timing of SBCE is thought to affect its diagnostic yield; however, the optimal timing remains unknown. Methods This retrospective study analyzed 131 patients with overt gastrointestinal bleeding managed with SBCE at our institution between May 2015 and December 2022. Patients were categorized into four groups based on the interval between their last bleeding episode and SBCE: 1–7, 8–14, 15–28, and ≥ 29 days. Results Positive findings were observed in approximately 50% of the cases across all intervals, with no statistically significant differences in the detection rates. Vascular lesions were detected primarily within 1–14 days, whereas inflammatory lesions, tumors, and diverticula were identified across all intervals. Notably, 25% of the patients with negative SBCE findings were later diagnosed with sources of non-small bowel bleeding, highlighting the value of follow-up endoscopic evaluations. Conclusions Our findings suggest that SBCE can be effective regardless of the time after a bleeding event, contrary to previous recommendations emphasizing its early use. Clinicians should consider performing SBCE whenever feasible to improve the diagnostic outcomes for gastrointestinal bleeding, irrespective of the elapsed time since the last episode.